2020
DOI: 10.3389/fevo.2020.00047
|View full text |Cite
|
Sign up to set email alerts
|

Behavior - Landscape Interactions May Create Super-Spreader Environments: Vigilance-Olfactory Interactions Across Land Type and Disease Transmission Potential in the Banded Mongoose

Abstract: A complex suite of drivers can influence infectious disease transmission with behavior and landscape spatial dynamics contributing importantly to epidemic patterns across host-pathogen-environmental systems. However, our understanding of the interaction between landscape and host behavior and its influence on spatial variability in pathogen transmission is limited. In the banded mongoose (Mungos mungo), a novel tuberculosis pathogen, Mycobacterium mungi, has emerged in Northern Botswana, which is transmitted t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 50 publications
(76 reference statements)
0
4
0
Order By: Relevance
“…Camera traps previously provided that landscape type variably influenced M. mungi transmission behaviours at the den site (Alexander & Nichols, 2020; Fairbanks et al, 2014). Our results showed that accelerometer‐derived data may also be used to identify these same mongoose behaviours critical to pathogen transmission across larger landscape areas.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Camera traps previously provided that landscape type variably influenced M. mungi transmission behaviours at the den site (Alexander & Nichols, 2020; Fairbanks et al, 2014). Our results showed that accelerometer‐derived data may also be used to identify these same mongoose behaviours critical to pathogen transmission across larger landscape areas.…”
Section: Discussionmentioning
confidence: 99%
“…We herein report the use of an Axy‐5X model accelerometer (TechnoSmArt) on captive mongoose as a proof‐of‐concept study to evaluate if accelerometers could be used to identify key mongoose behavioural activities relevant to M. mungi transmission. These behaviours included bipedal vertical vigilance, running and scent marking activity previously shown to vary across the landscape in this system (Alexander & Nichols, 2020). We also include evaluation of the data analytics and modifications to the data analysis works flows, updating and expanding upon current methodologies.…”
Section: Introductionmentioning
confidence: 96%
See 2 more Smart Citations